Measuring the Influence of Galilean Loupe System on Near Visual Acuity of Dentists under Simulated Clinical Conditions - Iris Urlić; Željko Verzak; Dubravka Negovetić Vranić (University of Zagreb. School of Dental Medicine, 2016)
Aim: The purpose of this study was to compare near visual acuity of dentists without optical aids (VSC) with near visual acuity of those using the Galilean telescope system (VGA2) with magnification of x 2.5, and the distance of 350 mm in simulated clinical conditions. Methods: The study included 46 dentists (visual acuity 1.0 without correction). A visual acuity testing was carried out using a miniaturized Snellen visual acuity chart which was placed in the cavity of molar teeth mounted in a phantom head in simulated clinical conditions. Near visual acuity for the vicinity was examined: 1) without correction at a distance of 300-400 mm (VSC); 2) with Galilean loupes with magnification of x2.5, focal length of 350mm. Results: The distributions of near visual acuity recorded using VSC and VGA2, 5 systems were compared by the Wilcoxon Signed Rank test. The results obtained by Wilcoxon Signed Rank test pointed to a statistically significant difference in the distribution of recorded visual acuity between the VSC and VGA2 optical systems (W = - 403.5; p <0.001). Conclusion: If using the VGA2, 5 systems, higher values of the near visual acuity were recorded and subsequently compared to near visual acuity without magnifying aids (VSC).